An Austrian in Hollywood. (8th March 2021) - Leinberger, Charles Francis
Abstract : When interviewed about film music, John Williams is often quick to credit Max Steiner as the originator of the leitmotif technique in film music. Steiner brought with him to the U.S. the compositional techniques he learned as a child prodigy in Europe, including the leitmotif technique. This paper will discuss Steiner's use of leitmotifs in his Academy Award winning score to the 1942 Warner Bros. film Now, Voyager. Film musicologists disagree on the relevance of themes being heard in different keys throughout a film score and their possible effect on the audience. I intend to demonstrate that, although the significance of these key relationships may only exist on a subconscious level, they do contribute in a meaningful way to the viewing/listening experience. To demonstrate this, I will use examples of "Charlotte's Theme, " also known as the "Love Theme, " which appears in various keys throughout the film. The key relationships are clearly intentional and well thought out by Steiner. This theme, which is almost always in triple meter, was recorded in 1943 by Allen Miller and his Orchestra as a pop tune, in quadruple meter, with the title "It Can't Be Wrong." Steiner plagiarizes himself when this instrumental version is heard as source music in the 1945 Warner Bros. film Mildred Pierce. Vocal versions, including one recorded by Frank Sinatra, include lyrics by Kim Gannon. This version was also sung in the Star Trek: Voyager episode "The Killing Game, Part 1."